A política dos cardeais : uma análise transnacional da atuação de Sebastião Leme e Manuel Cerejeira (1930/1945) - Oliveira, Alexandre Luís de (2018)
This thesis aims at the transnational investigation of the work of Cardinals Sebastião Leme da Silveira Cintra in Brazil and Manuel Gonçalves Cerejeira in Portugal as agents of Catholicism in the process of restoring the social and political role that the Church had lost with its implantation of Republicanism in their respective countries, and the practices of the secular State adopted. The analysis of this process of reconquest of space permeated the beginning of the trajectory of the two clerics, raising established networks as well as their insertion in the religious context as members of Catholicism as an institution. With different trajectories, Sebastião Leme, at the beginning of his seminary training, established a network close to the Rector, which enabled him to carry out part of his studies in Europe. On the other hand, Manuel Cerejeira developed a more academic formation that allowed the clergyman to approach the main political currents of Portugal of the beginning of the XX century, mainly during the time that attended the University of Coimbra. The analyzes also establish a survey of the performance of the main groups of conservative identity in both Brazil and Portugal and their possible relations with Catholicism. Also the groups created by the Church itself that aimed to group the laity Catholics to seek together with the Church a wider space for religious policies, among which in Portugal, the Portuguese Catholic Center, the Academic Center for Christian Democracy, Catholic Action that was established in both countries. In Brazil Catholicism had the support of the Dom Vital Center of the Catholic Confederations, as well as the Catholic Electoral League, which in the 1930s represented the political bias that the Church adopted to increase its freedom of action. In the 1930s the two religious were raised to cardinals and glimpsed in front of the Estado Novo. Beyond the peculiarities of the countries, politics represented a dictatorial period. The year 1945 came as a singular year for the end of the polls because it is a year of change. In the world scene represents the end of World War II, the peculiarities of Brazil are concentrated at the end of the period of Cardinal Leme, although deceased in 1942, the country only had a new cardinal in 1946. In Portugal the end of the War brought a new vision political and social. Even Salazar remaining in office, the vision of totalitarianism gained a new outfit.